Analisis Menurunnya Apresiasi Generasi Z Terhadap Kesenian Wayang di Desa Mangunsari Sebagai Sumber Pembelajaran IPS - Amanda Elena Ari Sabella; Siti Ekowati Rusdini (Pusdikra Publishing, 2026)
Wayang art is one of the local cultural heritages that embodies noble values and has the potential to serve as a learning resource in Social Studies education. As a traditional performing art, wayang does not only function as entertainment but also conveys moral messages, social norms, and philosophical teachings that reflect the cultural identity of Indonesian society. However, amid the currents of globalization, appreciation for wayang art has tended to decline, particularly among generation Z. This study aims to analyze the factors contributing to the decreasing appreciation of generation Z toward wayang art in Mangunsari Village and to examine its relevance to Social Studies learning. This research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation involving generation Z, community leaders, and wayang art enthusiasts. The findings indicate that the decline in generation Z appreciation is influenced by several factors, including differences in entertainment preferences, the lack of encouragement or invitation from the surrounding environment to watch wayang performances, and the limited relevance of wayang stories to the lifestyles of today’s youth. These conditions lead many young people to prefer modern digital entertainment rather than traditional cultural performances. Nevertheless, wayang art remains relevant to Social Studies learning competencies because it contains social, cultural, moral, and religious values that can support character education and cultural awarness. Therefore, wayang art can be integrated into Social Studies learning as an effort to preserve local culture while strengthening students understanding of social and cultural values in society.